Comparison of Pollen Grain Treatments Without Mechanical Fracturation Prior to Protein Quantification. Issue 4 (19th July 2021) - Westreich, Lila R; Tobin, Patrick C
Abstract: Protein and amino acids in pollen are important nutritional components for larval development in several insect species, especially in Apoidea. The Bradford assay is a widely used method to measure relative protein content of pollen, which can shed light on pollen quality and consequences to fitness. Prior to using the Bradford assay, protein must be released from pollen grains, often using a mixture of chemical and mechanical fracturation methods. In this study, we tested the efficacy of protein extraction without using mechanical fracturation. We used pollen collected by the solitary bee Osmia lignaria Say to compare two known buffers associated with pollen protein analysis: phosphate-buffered saline and sodium hydroxide, and deionized water, and with different pollen weights from which we quantified protein using the Bradford assay. While all buffers and deionized water were useful in releasing protein from pollen grains collected by O. lignaria, the use of sodium hydroxide resulted in significantly higher protein quantification across all pollen weights. This methodological study can inform future studies of pollen nutrition in pollen-foraging species.